Composite solid-state electrolyte membrane, preparation method and solid-state battery with composite solid-state electrolyte membrane

By using solid electrolyte particles of different particle sizes in the solid electrolyte membrane of solid battery to form a slurry and coated on the void matrix, the problems of high porosity and short circuit in the solid battery are solved, and further achievement High conductivity and yield.

CN119481260APending Publication Date: 2025-02-18ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411741918.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The internal porosity of the solid electrolyte membrane of solid state batteries is large, resulting in ion conduction blockage and short circuit, which reduces the yield rate of the battery.

Method used

Solid electrolyte particles of different particle sizes are stirred together with adhesive to form a solid electrolyte slurry, and coated on a substrate with a void, and enter the gap between large-particle size particles through small-particle size particles to reduce porosity.

Benefits of technology

It effectively reduces the porosity of the solid electrolyte membrane, improves the conductivity, reduces the short circuit phenomenon, and improves the yield and mechanical properties of the solid-state battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of solid-state batteries, and particularly discloses a composite solid-state electrolyte membrane, a preparation method and a solid-state battery with the composite solid-state electrolyte membrane. The composite solid electrolyte membrane comprises a substrate and a solid electrolyte, a gap is formed in the substrate, the substrate is coated with the solid electrolyte, at least part of the solid electrolyte enters the gap, and the solid electrolyte at least comprises a solid electrolyte with a first particle size and a solid electrolyte with a second particle size, the solid electrolyte with the first particle size and the solid electrolyte with the second particle size are bonded through an adhesive, a composite solid electrolyte membrane with low porosity is prepared, and the solid-state battery is obtained by using the composite solid electrolyte membrane. The matrix is filled with the solid electrolyte with different particle sizes, the internal porosity of the solid electrolyte membrane is effectively reduced, the conductivity of the solid electrolyte and the short circuit phenomenon of a solid battery are improved, meanwhile, the pores of the non-woven fabric are filled with the solid electrolyte material, and the mechanical property of the electrolyte membrane is improved by taking the non-woven fabric as a support.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid-state batteries, and in particular to a composite solid-state electrolyte membrane, a preparation method and a solid-state battery having the same. Background Art

[0002] As the next generation of lithium battery technology, solid-state batteries inherit the advantages of traditional lithium batteries and have outstanding advantages such as good safety and high energy density. However, solid electrolyte is a solid-phase material. Since the solid electrolyte particles cannot be in close contact with each other, the internal porosity of the solid electrolyte membrane is large and the internal ion conduction is blocked. At the same time, the large porosity of the solid electrolyte membrane can easily cause the solid-state battery to short-circuit, resulting in a low yield rate of solid-state batteries. Therefore, how to reduce the porosity inside the solid electrolyte membrane has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] The purpose of the present invention is to provide a composite solid electrolyte membrane, a preparation method and a solid-state battery having the same. The composite solid electrolyte membrane provided by the present invention can reduce the porosity in the solid electrolyte membrane.

[0004] In order to achieve the above purpose, the present invention adopts the following technical means:

[0005] The first aspect of the present invention provides a method for preparing a composite solid electrolyte membrane, comprising the following steps: providing at least two solid electrolyte particles having a first particle size and a second particle size, and stirring the solid electrolyte particles having the first particle size and the second particle size with a binder to form a solid electrolyte slurry; providing a substrate having voids inside, coating the solid electrolyte slurry on the substrate, and curing it.

[0006] In some embodiments of the present invention, D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from at least two within the range of 0.01 to 20 μm; preferably, D50 of the solid electrolyte particles is selected from at least two within the range of 0.1 to 5 μm.

[0007] In some embodiments of the present invention, D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from two of 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 3 μm and 5 μm.

[0008] In some embodiments of the present invention, the ratio of the number of solid electrolyte particles of the first particle size to the number of solid electrolyte particles of the second particle size is 0 to 1:1.

[0009] In some embodiments of the present invention, the solid electrolyte includes a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte.

[0010] Furthermore, the solid electrolyte is a sulfide solid electrolyte or a halide solid electrolyte.

[0011] In some aspects of the present invention, the adhesive is a rubber-based adhesive or a fluoride-based adhesive.

[0012] Furthermore, the rubber-based adhesive includes one or more of butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber, hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber and ethylene propylene rubber; preferably hydrogenated styrene butadiene rubber.

[0013] Furthermore, the fluoride-based adhesive includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-polyhexafluoropropylene copolymer, polytetrafluoroethylene and fluororubber.

[0014] In some embodiments of the present invention, the substrate is nonwoven fabric or paper.

[0015] Furthermore, the thickness of the substrate is 1-100 μm, and the porosity is 30%-80%. Preferably, the porosity is 50%-80%; more preferably, the thickness of the substrate is 15 μm, and the porosity is 80%.

[0016] A second aspect of the present invention provides a composite solid electrolyte membrane, comprising a substrate and a solid electrolyte, wherein gaps are formed in the substrate, a solid electrolyte is coated on the substrate, and at least a portion of the solid electrolyte enters the gaps, the solid electrolyte comprises at least a solid electrolyte of a first particle size and a solid electrolyte of a second particle size, and the solid electrolyte of the first particle size and the solid electrolyte of the second particle size are bonded to each other by an adhesive.

[0017] The present invention also provides a solid-state battery, comprising the composite solid electrolyte membrane obtained by the preparation method of the first aspect or the composite solid electrolyte membrane of the second aspect.

[0018] In the present invention, by selecting solid electrolytes of different particle sizes to form a solid electrolyte slurry and coating it on a matrix with voids, the solid electrolyte with a small particle size can enter the gaps of the solid electrolyte with a large particle size, thereby effectively reducing the internal porosity of the solid electrolyte membrane, improving the electrical conductivity of the solid electrolyte and the short circuit phenomenon; further, by using a matrix with voids, the solid electrolyte slurry can be formed not only on the surface of the matrix, but also enter the voids of the matrix, thereby improving the mechanical properties of the electrolyte membrane. DETAILED DESCRIPTION

[0019] Definition and explanation:

[0020] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as a minimum value and a maximum value, respectively.

[0021] In the numerical ranges recorded in stages in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment.

[0022] Unless the context clearly indicates otherwise, when used in this specification, the terms “comprises”, “comprising” and “includes” specify the presence of stated elements but do not exclude the presence or addition of one or more other elements.

[0023] As solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, hydride solid electrolytes, halide solid electrolytes, nitride solid electrolytes, etc. can be listed. Only one solid electrolyte can be used alone, or two or more can be used in combination. The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The hydride solid electrolyte preferably contains hydrogen (H) as the main component of the anion element. The halide solid electrolyte preferably contains a halogen element (X) as the main component of the anion element. The nitride solid electrolyte preferably contains nitrogen (N) as the main component of the anion element.

[0024] The binder of the present invention includes, for example, rubber-based binders, fluoride-based binders, etc. As rubber-based binders, for example, butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber (SEBS), nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, ethylene propylene rubber, etc. As fluoride-based binders, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, fluorine rubber, etc.

[0025] The nonwoven fabric of the present invention refers to a sheet-like product formed by bonding or entanglement of fibers without weaving, and means a planar fiber assembly having a predetermined level of structural strength obtained by a physical method and / or chemical method other than weaving, knitting and papermaking. The fiber assembly has a plurality of pores.

[0026] There is no particular limitation on the type of nonwoven fabric, and examples thereof include meltblown nonwoven fabric, spunbond nonwoven fabric, carded nonwoven fabric, parallel nonwoven fabric, cross-woven nonwoven fabric, random nonwoven fabric, spunlace nonwoven fabric, fast-spun nonwoven fabric, chemically bonded nonwoven fabric, water-entangled nonwoven fabric, needle-punched nonwoven fabric, stitch-bonded nonwoven fabric, thermally bonded nonwoven fabric, ruptured fiber nonwoven fabric, tow-opened nonwoven fabric, and film-split nonwoven fabric.

[0027] In some embodiments, the nonwoven fabric is selected from one or more of polyethylene nonwoven fabric, polypropylene nonwoven fabric, glass fiber nonwoven fabric, polytetrafluoroethylene nonwoven fabric, or cellulose nonwoven fabric.

[0028] The solid-state battery of the present invention is the following solid-state battery, comprising: a positive electrode layer containing a positive electrode active material; a negative electrode layer containing a negative electrode active material; and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, the solid electrolyte layer comprising the solid electrolyte membrane.

[0029] In the solid-state battery of the present invention, the positive electrode active material used in the positive electrode layer and the negative electrode active material used in the negative electrode layer are not particularly limited as long as they function as the positive electrode and the negative electrode of the solid-state battery.

[0030] The positive electrode and negative electrode constituting the solid-state battery are selected from two materials that can constitute electrodes, and the charge and discharge potentials of the two compounds are compared. The one showing a higher potential is used for the positive electrode, and the one showing a lower potential is used for the negative electrode, thereby constructing an arbitrary battery.

[0031] The solid-state battery of the present invention can be manufactured by disposing a solid electrolyte membrane including a solid electrolyte layer of the present invention between the positive electrode layer and the negative electrode layer, and bonding them together. There is no particular limitation on the bonding method, and examples thereof include a method of stacking and pressing each sheet, or a method of applying pressure between two rollers (roll to roll), etc.

[0032] Furthermore, in order to improve the adhesion between the solid electrolyte layer and the positive electrode layer or the negative electrode layer, an active material having ion conductivity or an adhesive material that does not inhibit ion conductivity may be disposed at the bonding interface.

[0033] The process, method and application of a composite electrolyte membrane provided in this application are described in detail below.

[0034] The purpose of the present invention is to provide a composite solid electrolyte membrane, a preparation method and a solid-state battery having the same. The composite solid electrolyte membrane provided by the present invention can reduce the porosity in the solid electrolyte membrane.

[0035] The method for preparing the composite solid electrolyte membrane provided by the present invention comprises the following steps:

[0036] S1: providing at least two solid electrolyte particles having a first particle size and a second particle size, and stirring the solid electrolyte particles having the first particle size and the second particle size with a binder to form a solid electrolyte slurry;

[0037] In this embodiment, the solid electrolyte particles of the first particle size and the second particle size are solid electrolyte particles of different particle sizes. Preferably, the D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from two of 0.8μm, 1μm, 1.2μm, 1.5μm, 2μm, 3μm and 5μm.

[0038] It should be noted that, in this embodiment, it can also provide solid electrolyte particles with more particle sizes. That is, in this embodiment, in the mixed solid electrolyte slurry, the particle size of the solid electrolyte particles will have a wider distribution, and the particle size D50 can be selected from at least two in the range of 0.01 to 20 μm. The ratio of the number of solid electrolyte particles of the first particle size and the second particle size is 0 to 1:1.

[0039] Furthermore, in this embodiment, the solid electrolyte can be a sulfide solid electrolyte, an oxide solid electrolyte or a halide solid electrolyte. That is, the solid electrolytes of two particle sizes can be a sulfide solid electrolyte, an oxide solid electrolyte or a halide solid electrolyte at the same time.

[0040] The binder can be a rubber-based binder, a fluoride-based binder, etc. As a rubber-based binder, for example, butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber (SEBS), nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, ethylene propylene rubber, etc. can be listed. As a fluoride-based binder, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, fluorine rubber, etc. can be listed. When in use, the binder can be first dissolved in a solvent, such as in isobutyl isobutyrate, and then mixed with the solid electrolyte.

[0041] Furthermore, during the mixing, the dew point temperature is less than -50° C. The solid electrolyte slurry can be obtained by stirring the mixture at a constant speed of 1400 rpm for 1 minute using a stirrer.

[0042] S2: providing a substrate having voids inside, coating the solid electrolyte slurry on the substrate, and curing the substrate to obtain a composite solid electrolyte membrane.

[0043] In this embodiment, the substrate can be a non-woven fabric or paper, the thickness of the substrate is 1 to 100 μm, and the porosity is 30% to 80%. Preferably, the porosity is 50% to 80%; more preferably, the thickness of the substrate is 15 μm and the porosity is 80%. It can be understood that after coating, the above-mentioned solid electrolyte slurry can enter the gaps in the substrate. Further, in this embodiment, the substrate coated with the solid electrolyte can be dried in an oven, and the drying temperature is greater than 60°C and the drying time is greater than 10 hours. During drying, the dew point temperature of the environment is less than -50°C, or nitrogen is filled into the environment for protection.

[0044] In this embodiment, by selecting solid electrolytes of different particle sizes to form a solid electrolyte slurry and coating it on a matrix with voids, the solid electrolyte with a small particle size can enter the gaps of the solid electrolyte with a large particle size, thereby effectively reducing the internal porosity of the solid electrolyte membrane and improving the electrical conductivity and short circuit phenomenon of the solid electrolyte; further, by using a matrix with voids, the solid electrolyte slurry can be formed not only on the surface of the matrix, but also enter the voids of the matrix, thereby improving the mechanical properties of the electrolyte membrane.

[0045] The present invention also provides a composite solid electrolyte membrane, which is prepared by the composite solid electrolyte membrane preparation method described above.

[0046] The composite solid electrolyte membrane includes a substrate and a solid electrolyte, wherein a gap is formed in the substrate, the solid electrolyte is coated on the substrate, and at least a portion of the solid electrolyte enters the gap. The solid electrolyte includes at least solid electrolyte particles of a first size and solid electrolyte particles of a second size, and the solid electrolyte particles of the first size and the solid electrolyte of the second size can be bonded by a binder.

[0047] Furthermore, in this embodiment, the solid electrolyte particles of the first particle size and the second particle size are solid electrolyte particles of different particle sizes, and D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from two of 0.8μm, 1μm, 1.2μm, 1.5μm, 2μm, 3μm and 5μm.

[0048] It can be understood that in this embodiment, it can also provide solid electrolyte particles with more particle sizes. That is, in this embodiment, in the mixed solid electrolyte slurry, the particle size of the solid electrolyte particles will have a wider distribution, and the particle size D50 can be selected from at least two in the range of 0.01 to 20 μm. The proportions of large, medium and small particle sizes of the solid electrolyte particles of the first particle size and the second particle size are 0-100% respectively.

[0049] The adhesive may be a rubber adhesive, a fluoride adhesive, etc. As the rubber adhesive, for example, butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene butadiene rubber (SEBS), nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, ethylene propylene rubber, etc. can be listed. As the fluoride adhesive, for example, polyvinylidene difluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, fluorine rubber, etc. can be listed.

[0050] The present invention also provides a solid-state battery having the above-mentioned composite solid-state electrolyte membrane. For other technical features of the solid-state battery, please refer to the prior art and will not be repeated here.

[0051] Example:

[0052] Example 1

[0053] S1: Weigh a certain amount of two sulfide solid electrolytes with particle sizes D50 selected from 5 μm (mass ratio: 50%) and 2 μm (mass ratio: 50%), put the above raw materials into the isobutyl isobutyrate solvent of SEBS binder and stir and mix them. In an environment where the dew point temperature is less than -50°C, the mixer is stirred at a constant speed of 1400 rpm for 1 minute to obtain a solid electrolyte slurry.

[0054] S2: The above slurry is evenly coated on the non-woven fabric with a thickness of 15 μm and a porosity of 80%, and then dried in an oven at 60°C for 24 hours. The dew point temperature of the environment should be kept below -50°C during the drying process, or nitrogen should be filled in the environment for protection. The solid electrolyte is fully and evenly distributed in the internal gaps of the non-woven fabric.

[0055] Example 2

[0056] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 5 μm and 1.5 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0057] Example 3

[0058] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 5 μm and 1.2 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0059] Example 4

[0060] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 5 μm and 1 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0061] Example 5

[0062] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 5 μm and 0.8 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0063] Example 6

[0064] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 3 μm and 2 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0065] Example 7

[0066] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 3 μm and 1.5 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0067] Example 8

[0068] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 3 μm and 1.2 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0069] Example 9

[0070] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 3 μm and 1 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0071] Example 10

[0072] The difference between this embodiment and embodiment 1 is that the particle sizes of the two sulfide solid electrolytes are selected from 3 μm and 0.8 μm, and the other preparation methods and conditions are the same as those in the embodiment;

[0073] Embodiment 11

[0074] The difference between this embodiment and embodiment 1 is that the particle sizes of the two solid electrolytes are halide solid electrolytes, and the other preparation methods and conditions are the same as those in the embodiment;

[0075] Comparative Example 1

[0076] S1: Weigh a certain amount of sulfide solid electrolyte with a particle size D50 of 5 μm, put the above raw materials into isobutyl isobutyrate solvent containing SEBS binder and stir and mix them. In an environment where the dew point temperature is less than -50°C, the stirrer is stirred at a constant speed of 1400 rpm for 1 minute to obtain a solid electrolyte slurry.

[0077] S2: The above slurry is evenly coated on the non-woven fabric with a thickness of 15 μm and a porosity of 80%, and then dried in an oven at 60°C for 24 hours. The dew point temperature of the environment should be kept below -50°C during the drying process, or nitrogen should be filled in the environment for protection. The solid electrolyte is fully and evenly distributed in the internal gaps of the non-woven fabric.

[0078] Comparative Example 2

[0079] Except that the sulfide solid electrolyte with a thickness of 2 μm was used instead of the sulfide solid electrolyte with a thickness of 5 μm in Comparative Example 1, the other operation steps were the same as those in Example 1, and an electrolyte membrane with a sulfide solid electrolyte was obtained.

[0080] Comparative Example 3

[0081] S1: Weigh a certain amount of halide solid electrolyte with a particle size D50 of 5 μm, put the above raw materials into isobutyl isobutyrate solvent containing SEBS binder and stir and mix them. In an environment where the dew point temperature is less than -50°C, the stirrer stirs at a constant speed of 1400 rpm for 1 minute to obtain a solid electrolyte slurry.

[0082] S2: The slurry is evenly coated on the non-woven fabric with a thickness of 15 μm and a porosity of 80%, and then dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment should be kept below -50°C, or nitrogen should be filled in the environment for protection.

[0083] Comparative Example 4

[0084] Except that the 2 μm halide solid electrolyte was used instead of the 5 μm halide solid electrolyte in Comparative Example 1, the other operation steps were the same as those in Example 1, and an electrolyte membrane with a halide solid electrolyte was obtained.

[0085] According to the above embodiment, a composite electrolyte membrane with low porosity is prepared, and an all-solid-state battery with excellent ion conductivity and not prone to short circuit is obtained by using the composite electrolyte membrane.

[0086] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0087] Test example:

[0088] The ionic conductivity, porosity, and cracking of the composite solid electrolyte membranes prepared in the above-mentioned embodiments and comparative examples were tested. The ionic conductivity was tested using an AC impedance tester, and the specific test conditions were: temperature 25°C, frequency 0.01-7MHz; anti-cracking performance: the composite solid electrolyte membrane was wound around a cylinder with a diameter of 1 cm, and visually inspected to see if cracking occurred. The test results are shown in Table 1.

[0089] Table 1 Electrochemical performance of examples and comparative examples

[0090] project Ionic conductivity (mS / cm) Porosity % Cracking condition (cylinder diameter: 1cm) Example 1 2.01 36.45 No cracking Example 2 1.93 34.12 No cracking Example 3 1.83 33.33 No cracking Example 4 1.79 33.11 No cracking Example 5 1.92 32.07 No cracking Example 6 1.89 35.69 No cracking Example 7 1.83 33.62 No cracking Example 8 1.88 33.21 No cracking Example 9 1.87 31.09 No cracking Example 10 1.84 30.18 No cracking Embodiment 11 1.87 38.65 No cracking Comparative Example 1 1.72 39.54 No cracking Comparative Example 2 1.55 33.11 No cracking Comparative Example 3 0.98 41.09 No cracking Comparative Example 4 0.61 33.43 No cracking

[0091] It can be seen from the above-mentioned experimental examples 1 to 11 and comparative examples 1 to 4 that filling solid electrolytes of various particle sizes in the non-woven fabric of the electrolyte membrane can improve the conductivity of the electrolyte membrane more than solid electrolytes of a single particle size. At the same time, the solid electrolyte material is filled in the pores of the non-woven fabric. Under the reference of the solid electrolyte of the same particle size, the smaller the particle size used, the lower the porosity of the electrolyte membrane, and the electrolyte membrane does not crack.

[0092] Specifically, when using solid electrolytes of various particle sizes, the smaller particle size solid electrolyte can be filled into the larger particle size solid electrolyte. Then, when the obtained electrolyte membrane is applied to the solid-state battery, the porosity of the electrolyte membrane can be reduced, the conductivity of the solid-state battery can be improved, and the low conductivity and short circuit of the solid-state battery can be solved. In addition, the use of non-woven fabric as support improves the mechanical properties of the electrolyte membrane, and the solid-state battery no longer has defects such as "broken" and "cracked", which improves the yield rate of the solid-state battery.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The steps include: Providing at least two solid electrolyte particles having a first particle size and a second particle size, and stirring the solid electrolyte particles having the first particle size and the second particle size with a binder to form a solid electrolyte slurry; A substrate with voids inside is provided, the solid electrolyte slurry is coated on the substrate, and then cured.

2. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from at least two types within the range of 0.01 to 20 μm.

3. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The D50 of the solid electrolyte particles of the first particle size and the second particle size is selected from two of 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 3 μm and 5 μm.

4. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The ratio of the number of the solid electrolyte particles having the first particle size to the number of the solid electrolyte particles having the second particle size is 0 to 1:

1.

5. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The adhesive is a rubber-based adhesive or a fluoride-based adhesive.

6. The method for preparing a composite solid electrolyte membrane according to claim 5, characterized in that: The rubber-based adhesive includes one or more of butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber, hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber and ethylene propylene rubber; the fluoride-based adhesive includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-polyhexafluoropropylene copolymer, polytetrafluoroethylene and fluororubber.

7. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The substrate is nonwoven fabric or paper.

8. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The thickness of the matrix-free body is 1 to 100 μm, and the porosity is 30 to 80%.

9. A composite solid electrolyte membrane, characterized in that: It includes a substrate and a solid electrolyte, wherein a gap is formed in the substrate, the solid electrolyte is coated on the substrate, and at least a portion of the solid electrolyte enters the gap, the solid electrolyte includes at least a solid electrolyte of a first particle size and a solid electrolyte of a second particle size, and the solid electrolyte of the first particle size and the solid electrolyte of the second particle size are bonded by an adhesive.

10. A solid-state battery, characterized in that: Comprising the composite solid electrolyte membrane of claim 9.

Citation Information

Cited By

  • Solid-state battery composite positive electrode based on grain size distribution and step-by-step mixing technology and preparation method of solid-state battery composite positive electrode

    CN121769016A